O diretor de escola e a elaboração do projeto políticopedagógico : o pensar e o agir - Monteiro, Aneridis Aparecida (Universidade Federal de São Carlos, 2003)
This work has objective to examine the conceptions of de school directors how much the elaboration of the political-pedagogical projects in these schools. When examining its conceptions, search to understand and to reflect the paper of the school director in this process, as well as its position and interference. In accordance with de Law 9.394/96, each school must elaborate its pedagogical proposal. One of the requirements for this elaboration in the collective participation of involved actors in the pertaining to school process, amongst them, the parents, teachers, students, beyond, of the direction of the school. The objective of this work is to focus if it had, what was the participation of these actors, and also which the difficulties and/or facilities for the elaboration of the political-pedagogic project. In the search of the information, bibliographical research was carried through to anchor the treated and an empirical research, opting itself to a qualitative boarding of researched, in which the data has been collected by verbal story of the school directors. The research was carried in publishes state and municipal schools of the city of Araras, São Paulo, privileging schools with basic education. After done the data analysis and consideration searched to verify to thoughts or either, what the interviewed school directors think and understand on the political pedagogical project, and the act, or as the school directors the have acted for elaboration of the related projects.
Keywords: Gestão educacional; Projeto político-pedagógico; Gestão escolar; Autonomia na escola; CIENCIAS HUMANAS::EDUCACAO